Risk of Antiepileptic Drug Withdrawal in Tuebrous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Of 122 children with tuberous sclerosis complex (TSC) followed at Texas Scottish Rite Hospital for Children, Dallas, TX, 106 (86.9%) had a history of epilepsy.